The Transportation Problem Under Probability and Fuzzy Uncertainties (Bangladesh Journal of Scientific and Industrial Research, 2011)
The paper presents the more developed approach for the transportation problem solution in the case of fuzzy co-efficients. The implementation of fuzzy extension of general simplex method is used to realize the numerical fuzzy optimization with fuzzy constraints. The proposed fuzzy numerical method is based on the practical system of the Pioneer Stefan Chanas idea to consider the fuzzy numbers in the probabiilistic sense. The solution of the problem is more generalized based upon the distributor's benefit maximization. Key words: Transportation problem; Fuzzy co-efficients; Fuzzy optimization; Transporting costs; Practical system. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8193 Bangladesh J. Sci. Ind. Res. 46(2), 247-254, 2011